Novel Donor p-Acceptor Conjugates-Functionalized Zinc Phthalocyanines Application in Dye-Sensitized Solar Cells - Zhang, Xuejun; Wang, Meiling; He, Huipeng; Mao, Lijun (Asian Journal of Chemistry, 2014)
New zinc phthalocyanines [2-(N,N-bisacetic acid amino)-9,16,23-(N,N-bisethylamino)zinc phthalocyanine (SPC), 2-(N,N-bisacetic acid amino)-9,16,23-(N,N-bispropyl-amino)zinc phthalocyanine (TPC), 2-(N,N-bisacetic acid amino)-9,16,23-(N,N-bisbutylamino)zinc phthalocyanine (FPC)], functionalized with donor-p-acceptor conjugates were synthesized, The new compounds were characterized using FTIR, UV-visible, 1H NMR, cyclic voltammetry, differential pulse voltammetry and elemental analysis. From the reduction and oxidation behaviour, it is proved that SPC, TPC, FPC have negative LUMO levels and positive HOMO levels, satisfying the energy gap rule, they can be employed as sensitizers for dye-sensitized solar cells and their optical, electrochemical and photovoltaic properties were also studied. They exhibited broad absorption adsorbed onto a 6 μm thick TiO films. The photovoltaic devices produced short circuit current densities of 1.53, 2.07, 1.89 mA/cm2, the open circuit voltage of 0.48, 0.55, 0.56 V and power conversion efficiency of 1.42, 1.67, 1.64 % respectively under AM1.5G illumination.